Research on the mechanical properties and mechanism of alkali-activated saline soil composite materials. (11th June 2018) - Hai-yan, Yu; Juan, Zhao; Jiu-jun, Yang; Yong-qiang, Li
ABSTRACT: Saline soils, which are mainly found in the arid/semi-arid climatic areas and coastal regions, are widespread all of the world, having limited potential for cultivation. This paper presents a study explored an alternative way by using alkali activated saline soil combined with fly ash to form geopolymer to develop the building materials with ultra-low embodied energy and CO2 for sustainable construction. The properties of the alkali-activated geopolymer made with saline soil-fly ash combination were evaluated. With the study on the effects of the mix proportions and process technics, the production of the geopolymer was optimised. The study indicates that the ideal conditions for the dissolution of SiO2 and Al2 O3 were 10M NaOH at 60°C for 24 hours. The saline soil-fly ash combination has good physical and mechanical properties and durability, which were increased with the fly ash content from 20% to 60%. XRD, FTIR and SEM were applied to analyse the reaction mechanism and microstructures of the alkali-activated saline soil-fly ash system. After alkali-activation, depolymerisation and reconstruction of the activated silicate and aluminate formed zeolite-liked gel products and generated aluminium silicate network structures, which is the key for the performance of the material obtained. The microstructure of product varied with the fly ash content in the system, affecting the density of the products.